Proton pump inhibitor medication is associated with colonisation of gut flora in the oropharynx. Issue 6 (8th March 2018) - Tranberg, A.; Thorarinsdottir, H. R.; Holmberg, A.; Schött, U.; Klarin, B.
Abstract : Background: The normal body exists in mutualistic balance with a large range of microbiota. The primary goal of this study was to establish whether there is an imbalance in the oropharyngeal flora early after hospital or ICU admittance, and whether flora differs between control, ward and critically ill patients. The secondary goal was to explore whether there are patient characteristics that can be associated with a disturbed oropharyngeal flora. Methods: Oropharyngeal cultures were obtained from three different study groups: (1) controls from the community, (2) ward patients and (3) critically ill patients, the two latter within 24 h after admittance. Results: Cultures were obtained from 487 individuals: 77 controls, 193 ward patients and 217 critically ill patients. Abnormal pharyngeal flora was more frequent in critically ill and ward patients compared with controls (62.2% and 10.4% vs. 1.3%, P  <   0.001 and P  =   0.010, respectively). Colonisation of gut flora in the oropharynx was more frequent in critically ill patients compared with ward patients or controls (26.3% vs. 4.7% and 1.3%, P  <   0.001 and P  <   0.001, respectively). Proton pump inhibitor medication was the strongest independent factor associated with the presence of gut flora in the oropharynx in both ward and critically ill patients ( P  = 0.030 and P  = 0.044, respectively). Conclusion: This study indicates that abnormal oropharyngeal flora is an early and frequent event in hospitalised patients and more so in the critically ill, compared to controls. Proton pump inhibitor medication is associated with colonisation of gut flora in the oropharynx.